PENGATURAN PENETAPAN (PENARIKAN) PAJAK ATAS TRANSAKSI JUAL BELI MELALUI ELEKTRONIC COMMERCE DALAM KAITANNYA DENGAN UU NO 28 TAHUN 2007 DAN UNCITRAL MODEL LAW OF ECOMMERCE 1996 - DADANG YUSUF JUHAENI DADANG YUSUF JUHAENI (POLITEKNIK PIKSI GANESHA, 2019)
The purpose of this study is to observe and know the supervision of tax collection and the authority of Indonesian taxation to collect taxes on sale and purchase transactions using e-commerce transactions according to Indonesian laws involving cross-country which can increase state revenue in the context of financing development where Indonesia has made taxation agreements with other countries. The method used is descriptive analytical and qualitative juridical with collection techniques data using document studies and interviews. The results are aimed at collecting taxes on buying and selling transactions, there needs to be supervision, especially for buying and selling transactions conducted through e-commerce, including supervision in Value Added Tax (PPN), based on the provisions of Article 11 of the 1945 Constitution, the legal position of the tax treaty is the same as the National Law such as the Law on Income Tax. The legal position of the tax treaty is no higher than the National Taxation Law. Thus it is concluded that a tax collection system is an essential function of the state, a function that is needed for the continuation or survival of the state, so that the consequences are that the tax is a means used by the state for the purpose of collecting and putting as much money into the state treasury, which in the taxation literature called the function of the budgeter, where the tax collection is used to increase state revenue in the framework of development financing, so that transactions through e-commerce are a large tax potential for state revenue in the context of development.